PENDIDIKAN AGAMA ISLAM PESANTREN BERBASIS PENGEMBANGAN KECERDASAN SPIRITUAL SISWA DI SMP WAHID HASYIM - Wardah Fatchah Azzahwa; Muhammad Arif Syihabuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This studyaims to analyze the strategies and implementation of Islamic Religious Education (PAI) based on Islamic boarding schools in developing the spiritual intelligence of students at Wahid Hasyim Junior High School. The study uses a qualitative approach with a case study type to gain an in-depth understanding of the process, strategies, and practices of PAI learning in the context of school life. Data collection techniques were conducted through interviews, observation, and documentation. The results of the study showed that the development of students' spiritual intelligence was carried out through four main strategies, namely the habit of worship (dhuha prayer, congregational prayer,memorization of Juz 30, and worship practices), integration of spiritual values in each PAI subject (fiqh, aqidah akhlak, and the Qur'an), the application of contextual learning, and the strengthening of the school's religious culture, such as pilgrimage activities to the tomb of KH. Wahid Hasyim in Jombang. This implementation not only improves students' cognitive understanding of Islamic teachings, but also encourages the internalization of spiritual values in daily life such as discipline, responsibility, empathy, and noble character. Thus, this pesantren-based PAI model has proven effective in forming a balance between students' intellectual and spiritual aspects and can be a strategic alternative in strengthening character education in formal educational institutions.